Linggui Zhugan Formula Improves Glucose and Lipid Levels and Alters Gut Microbiota in High-Fat Diet-Induced Diabetic Mice - Wu, Rui; Zhao, Dandan; An, Ran; Wang, Zhufeng; Li, Yuxiu; Shi, Bai; Ni, Qing (Frontiers in Physiology, 2019)
Background: The gut microbiota plays important roles in the occurrence and development of obesity and diabetes through participating in nutrient absorption and metabolism. Microecological regulation is likely to be key to understanding the effects of Chinese medicine. The Linggui Zhugan (LGZG) formula is a well-known Chinese medicine for controlling obesity in the clinic. However, its pharmacological effects and mechanism of action in diabetes require further exploration. Objective: To evaluate the effects of LGZG on body weight, glycemic control, lipid levels and gut microbiota in high-fat diet-induced diabetic mice. Methods: High-fat diet-induced diabetic mice were subjected to an 8-week protocol of LGZG administration. We then evaluated the pharmacological effects of LGZG and its influence on gut microbes in fecal samples using the 16S rRNA-based microbiome profiling technique. Results: LGZG administration significantly reduced body weight and body fat mass in diabetic mice. Compared with the high-fat diet control group, LGZG favorably influenced blood glucose control, decreased blood glucose levels and increased glucose tolerance, accompanied by an improvement in lipid metabolism. Furthermore, the global community composition and relative abundance of many taxa differed between mice fed chow or a high-fat diet. As expected, LGZG supplementation altered the general community structure of gut microbiota, the Firmicutes/Bacteroidetes ratio, and the relative abundance of certain bacteria, such as Bacteroides, Lactobacillus, Oscillospira and Helicobacter. Conclusion: LGZG effectively controlled obesity and relieved insulin resistance, which may be closely related to its impact on gut microbiota.